Modernity of slavery : struggles against caste inequality in colonial Kerala - Sanal Mohan, P. (Oxford University Press, 2015)
Modernity of Slavery tells the story of Cherumas, Kuravas, Parayas, Pulayas, and Thanda Pulayas the slave castes of nineteenth-century Kerala and their tryst with Christianity. These castes comprised nearly one-sixth of the population and were 'owned' by upper castes, princely states, and even Europeans. In the nineteenth and twentieth centuries, when European missionaries began working among the slave castes, thousands joined the Church. Their generational experiences, struggles, and memories shaped their collective self, and deeply impacted the emergence of Dalit consciousness in Kerala. This book presents and analyses the imaginations and articulations of the notion(s) of equality in the context of caste slavery, missionary activity, and socio-political transition in pre-colonial and modern Kerala. Centring the questions of consciousness and interiority, this book challenges the stereotypes of historical writing on Dalits and Christianity. It highlights everyday experiences, such as break-up of families, torture, sufferings, and re-memorialization of these experiences by contemporary generations, and weaves in narratives of specific instances, events, and personalities. Offering nuanced and unprecedented use of fresh archival sources and historical ethnography, this book will be a tour de force for anyone interested in the journeys of Dalit consciousness, Christianity, and religious movements in India.